The Attitude of New Political Parties in Poland towards Religion and the Catholic Church Based on the Example of Left-Wing Parties - Kancik-Kołtun, Ewelina; Wallner, Michał; Michalczuk-Wlizło, Marta (Historia i Polityka, 2022)
In recent years, the issue of the relationships between the state and the Catholic Church has been increasingly present in public discourse in Poland. New political parties have become embroiled in the debate, taking diverse stances. The paper discusses the attitude of new political parties in Poland towards religion and the Catholic Church, using three groupings as examples: the Palikot Movement [Ruch Palikota], Robert Biedroń’s Spring [Wiosna Roberta Biedronia] and the Together Party [Partia Razem]. The authors, using content analysis as the research method, reviewed the party policies and media statements made by politicians on the topic. The aim of the article is to investigate the positions taken by selected political parties towards religion and the Catholic Church and to verify the hypothesis that the new left-wing parties advocate a strict separation of church and state.